Strategi Pemasaran Biro Perjalanan Haji dan Umroh dalam Meningkatkan Minat Calon Jemaah - Maharani, Mega Utami; Sadiah, Dewi; Mujib, Abdul; Mulqiyah, Hilma (Mabrur: Academic Journal of Hajj and Umra, 2022)
This study aims to determine the marketing strategy and how to implement the marketing strategy carried out by Ghinasepti Tour and Travel in attracting the interest of prospective pilgrims. The method used is descriptive method with a qualitative approach. The results of this study indicate that first, the formulation of a marketing strategy which includes the vision and mission, analysis of the internal and external environment using SWOT analysis, and the determination of marketing strategies based on the marketing mix. Second, the implementation of a marketing strategy based on a marketing communication strategy. Third, the evaluation of the marketing strategy carried out by Ghinasepti uses two techniques: a. By evaluating the technical implementation of activities in disseminating information through marketing communication media that have been carried out, b. By evaluating the sources of information obtained by prospective pilgrims.